Citizenship and Democracy in the Texas Social Studies Curriculum: A Historical Comparison - Lambert, Jarod M. (International Journal of Social Learning (IJSL), 2024)
Using exploratory qualitative document analysis, this article examines the conceptions of citizenship and democracy in Texas's social studies curriculum standards. In a historical comparison of standards from 2011 and 2018, conceptions of citizenship and democracy are compared to definitions developed by international civic education experts. Citizenship and democracy in the Texas curriculum are identified as inconsistent with the definitions of those terms developed by civic education experts. Instead, the terms are seen to be related to Barber’s (1984/2003) thin democracy and procedural conceptualizations of citizenship. Moreover, conceptions of the terms remain the same from 2011 to 2018. Implications for teacher education and public school practice are discussed. Recommendations for future research are presented. Included among recommendations for future research is the analysis of curriculum documents in additional U.S. states and curriculum documents in countries outside the United States.